Pembelajaran Mufrodat dengan Metode Bernyanyi Anak Kelas B RA Perwanida XXV Wonogiri - Ulinnuha Nafisah Nuri Salma (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2023)
The Selection of Methods in Mufrodat (Vocabulary) Learning Is Very Important for Early Childhood Education. A good and appropriate method will help children easily remember the vocabulary they have learned. This research was conducted to examine the process of mufrodat learning using the singing method, to assess the learning outcomes of mufrodat through the singing method for children, and to identify the supporting and inhibiting factors in using the singing method for mufrodat learning. This study used a Classroom Action Research (CAR) approach with a descriptive qualitative design. The research subjects were Class B children at RA Perwanida XXV Wonogiri, consisting of 1 girl and 8 boys. Data collection methods included interviews, observations, and documentation. Based on the collected data, it can be concluded that mufrodat learning using the singing method is considered effective for early childhood. The research results showed that many children were able to memorize 7 vocabulary words (mufrodat) and achieved the BSH (Developing as Expected) rating, measured using a checklist on the children’s vocabulary assessment indicator sheet. In the mufrodat learning process with the singing method, the implementation was combined with explaining the meaning of each vocabulary word. Therefore, it can be concluded that mufrodat learning using the singing method can increase the desire and activeness of Class B children at RA Perwanida XXV Wonogiri in the 2023/2024 academic year in learning vocabulary. The supporting factors of mufrodat learning with the singing method are: helping children stay active, training them to focus, and building their self-confidence. Meanwhile, the inhibiting factors are: it requires quite a long time, and some children may remain inattentive or refuse to sing.